Nutrient composition of lotus (Nelumbo nucifera) fruits (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
The Nelumbo nucifera known as sacred lotus is an ornamental plant having medicinal possessions. Lotus seeds, which are currently the oldest known plant seeds, contain many functional constituents. The seeds have been widely used as both medicine and food. In the present studies, the nutrient composition of collected from two separate beels at Tarakanda, Mymensingh were determined. The nutrient composition was determined as moisture 17.727 (± 0.053), ash 9.49 (± 0.059), crude protein 16.563 (± 0.076), crude lipids 4.146 (± 0.038), crude fiber 7.755 (± 0.045), carbohydrate 44.042 (± 0.011). The results showed that lotus seeds contained a high content of moisture, crude protein, crude lipids, crude fiber, ash and carbohydrate. From this research, it found that lotus seeds were rich in crude protein and carbohydrate. The study may conclude that seeds could be incorporated in feed formulation as a source of nutrients. The present experiment may provide a guideline for the use of lotus seeds as human food.Asian Australas. J. Biosci. Biotechnol. 2020, 5 (3), 115-120